A Reflection on the Conservation of Waterlogged Wood: Do Original Artefacts Truly Belong in Public Museum Collections? - Miran Erič; David Stopar; Enej Guček Puhar; Lidija Korat Bensa; Nuša Saje; Aleš Jaklič; Franc Solina (Heritage, 2025)
The last decade has seen a transformative advancement in computational technologies, enabling the precise creation, evaluation, visualization, and reproduction of high-fidelity three-dimensional (3D) models of archaeological sites and artefacts. With the advent of 3D printing, both small- and large-scale objects can now be reproduced with remarkable accuracy and at customizable scales. Artefacts composed of organic materials—such as wood—are inherently susceptible to biological degradation and thus require extensive, long-term conservation employing costly methodologies. These procedures often raise environmental concerns and lead to irreversible alterations in the wood’s chemical composition, dimensional properties, and the intangible essence of the original artefact. In the context of public education and the dissemination of knowledge about historical technologies and objects, 3D replicas can effectively fulfill the same purpose as original artefacts, without compromising interpretative value or cultural significance. Furthermore, the digital data embedded in 3D surface and object models provides a wealth of supplementary information that cannot be captured, preserved, or documented through conventional techniques. Waterlogged wooden objects can now be thoroughly documented in 3D, enabling ongoing, non-invasive scientific analysis. Given these capabilities, it is imperative to revisit the philosophical and ethical foundations of preserving waterlogged wood and to adopt innovative strategies for the conservation and presentation of wooden artefacts. These new paradigms can serve educational, research, and outreach purposes—core functions of contemporary museums.